Action Mechanisms of Plant Growth Promoting Cyanobacteria in Crops In Situ: A Systematic Review of Literature (2020)
ABSTRACT : Background and Aims. An excessive and prolonged use of fertilizers undermines soils’ quality and, consequently, that of the crops they support, thus reducing the content of organic matter and generating environmental damages and problems to human health. ,erefore, the use of biofertilizers such as cyanobacteria becomes a promising alternative. However, it is not always possible to generalize these fertilizers’ applicability, because microorganisms may be impacted by the physical and chemical variations of their environment. We will describe the action mechanisms or the characteristics of cyanobacteria involved in plant growth promotion for different crops in situ through a systematic review of scientific literature. Methods. A comprehensive search for original articles in two different databases, ScienceDirect and Scopus, was performed. We included in our search documents published from 2009 to 2018. After the screening process and the addition of gray literature publications, we obtained 23 articles for theoretical analysis. Results. ,e studies were distributed mainly in Asia and part of Africa, without any important temporal variation. ,ey also showed a tendency to describe the use of cyanobacteria genera such as Anabaena sp., Nostoc sp., and Calothrix sp., besides mechanisms as N2 fixation, phosphate solubilization, phytohormone production, bioactive compounds excretion, and symbiotic associations, mainly on rice, wheat and corn crops. Conclusions. Cyanobacteria fertilizers used in situ are a widespread strategy, mainly in cereal crops. ,eir use is predominant in countries where cereal crops make an important contribution to their national economy. ,e great variety of mechanisms and characteristics of cyanobacteria used to promote plant growth in the field demonstrate the dramatic influence that physical, chemical, and biological variables have in their development.